Kritik Sastra dalam Cerpen Orang-orang dari Selatan Harus Mati Malam Itu karya Faisal Oddang: Suatu Pendekatan Sosiologi Sastra - Eka Sri Pratiwi; Siti Muntapiroh; Ahmad Supena (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
Literary works serve as an effective medium for expressing critiques of social issues within a community. The short story Orang-Orang dari Selatan Harus Mati Malam Itu by Faisal Oddang portrays instances of oppression and violence experienced by the Tolotang minority group. This study aims to examine the various forms of social criticism present in the story through a sociological approach to literature. The research applies a qualitative descriptive method, with data gathered through literature review, close reading, and note-taking techniques. Content analysis is employed to interpret the data. The findings indicate that the short story addresses themes of authoritarian rule, dehumanization, systemic violence, information control, public resignation, and the erasure of cultural identity. The narrative reveals how power can function repressively, undermining both diversity and human dignity. As such, this story stands not only as a literary creation but also as a symbolic critique of oppressive power structures.